SLOPE OBSERVATION OF THE PADANG SOLOK ROAD AREA BASED ON RADAR DATA - Marsa, Indira; Razi, Pakhrur; Akmam; Nishi, Katsunoshin (EarthCare, 2024)
The Padang Solok route topographically has a geological structure that is prone to steep slopes, so it has a high level of disaster risk, one of which is shifting soil and causing landslides. Slope is one of the factors that cause landslides, the purpose of this study is to determine the slope that is prone to landslides. However, slope information needs to be known the slope, and we can know the percentage and degree by mapping using satellite radar SAR (Syntetic Aperture Radar) technology, which is an effective choice for detecting the earth's surface in the Padang-Solok area with SRTM data taken in the area. Processed by observing the slope of the area and then analyzing the landslide area. SAR radar satellite technology allows monitoring of landslide-prone areas with high accuracy, and wide area coverage, operating day and night. This slope is a comparison of height in the form of the vertical distance of a land with its horizontal distance. The amount of slope can be expressed in several units, including percent and degree. Spatial information on slope describes the condition of the land surface, such as a flat, gentle, or steep slope. The Padang-Solok route includes steep slope areas with the highest slope of 7,9 to 40,8 and in percentage 13,80% to 90,10%, classified as steep and steep slope. Areas with steep slopes have a greater potential for landslides than those with moderate slopes, in addition to increasing the amount of surface flow. So the steeper the slope, the greater the velocity of surface flow, and thus the greater the water transport energy.